BS ISO 3951-6. Sampling procedures for inspection by variables. Part 6. Specification for single sampling plans indexed by limiting quality (LQ) for isolated lot inspection for a single quality characteristic and a single LQ (11th June 2021) - British Standards Institution
No abstract available